Analyzing the Business Performance of An Erp Systems in Automotive Ancillary Industries-Balanced Scorecard Perspective - Lakshmanan, Srinivasan; Edmund Christopher, S.; Kinslin, D. (International Journal of Engineering and Technology, 2018)
This study aims to analyze the business performance of Enterprise Resource Planning (ERP) system in Automotive Ancillary Industries using four interrelated dimensions of performance measurement framework Balanced Scorecard (BSC); Innovation and Learning, Internal, Customer and Financial perspective. This analysis was carried out based on survey questionnaires with 281 stakeholders who are familiar with ERP system and results were presents as evidence. The analysis result shows that uses of ERP system resulted in a positive in financial performance of the organization, deliver best services to their customer, increases the overall internal performance of the firm increases and enhances firm loyalty and simplify the complex work. Friedmanâ€™s ranking analysis and correlation analysis were applied, and detailed analysis was submitted in this study. The results from the survey indicate that integrated software system such as ERP need to be implemented in Automotive Ancillary Industries to improve the business performance in various dimension i.e. Innovation and Learning, Internal, Customer and Financial perspective.Â Â